2018
DOI: 10.1155/2018/1858241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bleeding Symptoms among Adolescents and Young Adults in the Capital City of Saudi Arabia

Abstract: Background Bleeding disorders vary in prevalence. While some are rare, some can be common in both sexes. Most bleeding disorders manifest as chronic bleeding tendencies or as an increase in bleeding during surgical procedures or trauma. The consequences of bleeding can be as simple as iron deficiency or catastrophic, resulting in severe morbidity and mortality. Bleeding disorders typically affect both sexes except hemophilia A and B, which mainly affects males. Method We conducted a questionnaire-based survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
(23 reference statements)
1
16
1
Order By: Relevance
“…The prevalence of bleeding disorders in most Arab countries including Saudi Arabia is unknown; however, from clinical practice, it seems they are relatively higher, probably due to concentration of the mutated genes and increased consanguineous marriages. In our limited bleeding surveillance study, which looked at the bleeding symptoms of about 4000 adolescents and young adults, we observed that about 20% have one or more bleeding symptoms and up to 10% iron deficiency mainly in females . The reported cases of some of the bleeding disorders like Glanzmann's thrombasthenia showed up to fivefold increase in Saudi Arabia than the international prevalence…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of bleeding disorders in most Arab countries including Saudi Arabia is unknown; however, from clinical practice, it seems they are relatively higher, probably due to concentration of the mutated genes and increased consanguineous marriages. In our limited bleeding surveillance study, which looked at the bleeding symptoms of about 4000 adolescents and young adults, we observed that about 20% have one or more bleeding symptoms and up to 10% iron deficiency mainly in females . The reported cases of some of the bleeding disorders like Glanzmann's thrombasthenia showed up to fivefold increase in Saudi Arabia than the international prevalence…”
Section: Discussionmentioning
confidence: 95%
“…While most known inherited bleeding disorders are hemophilia A and B, they are relatively rare. 12 Most MBDs are often unrecognized as patients bleed only during stress periods, surgery, or medical procedures. 12 In Saudi Arabia, other than case reports and case series, no large scale population-based screening studies have reported the prevalence of bleeding disorders.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Most MBDs are often unrecognized as patients bleed only during stress periods, surgery, or medical procedures. 12 In Saudi Arabia, other than case reports and case series, no large scale population-based screening studies have reported the prevalence of bleeding disorders. 8 13 14 Arab population may have a higher prevalence of bleeding disorders than Western population, owing primarily to a higher consanguinity in Arab communities.…”
Section: Discussionmentioning
confidence: 99%
“…A shorter version of the questionnaire was derived from the same Arabic version of the MCMDM-1 questionnaire with less details to be used as an initial screening tool. [ 18 ] Our primary outcome was any symptom of bleeding tendency. In this regard, the questionnaire was designed to address the following: Epistaxis, Cutaneous symptoms, bleeding from Minor Wounds, Oral Cavity Bleeding, Gastrointestinal Bleeding, Bleeding after First Surgery, and Muscle Hematomas/Hemoarthrosis.…”
Section: Methodsmentioning
confidence: 99%
“…In the current survey, we aimed to estimate the prevalence of bleeding tendency symptoms among a sample of adolescent university students in Almadinah Almunawwarah, and we are following the same methodology with permission, as in the study published in 2018 by Owaidah et al . [ 18 ] aiming to extend the results to cover another sample of the population in western region of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%